Research Potential of Center of Ethnology and Anthropology of the Contemporary, Polish Academy of Sciences, Warsaw, and the Prospects of Scientific Cooperation with Folklorists and Ethnologists of the National Academy of Sciences of Ukraine - Kość-Ryżko, K.; Tangad, O. (Народна творчість та етнологія, 2019)
The article is dedicated to the centenary celebration of the Ukrainian National Academy of Sciences. The importance of the Polish-Ukrainian borderlands investigation is emphasized. The collaboration of PAS and NASU in this direction is analyzed. Mainly, attention is paid to research trends of the Center of Ethnology and Anthropology of the Contemporaneity PAS. In particular, the studies on religiousness, worship, and secular rituals by PhD Kamila Baraniecka-Olszewska, ethnic, migration, and transcultural investigations by Dr hab Katarzyna Kość-Ryżko, and the issues of the history of the research on Mongolia analyzed and continued by PhD Oyungerel Tangad are described.